A field measurement of temperature and humidity in a utility tunnel and a brief analysis of the exhaust heat recovery system. Issue 4 (April 2021) - Tai, Chuanmin; Tian, Guansan; Lei, Wenjun; Wang, Jianwei
Underground utility tunnels (UUTs) are important components of infrastructure and 'lifelines' that ensure urban operations. Temperature and humidity are the main parameters that affect the performance of heat recovery utilization systems in underground spaces. In this study, temperature and humidity measurements were conducted in a UUT in northern China during winter. The results showed that the winter temperature in the UUT was relatively high and constant, and could be maintained above 8.5°C. The relative humidity (RH) in the UUT varied widely but could be kept below 65%. Based on the analysis of the test results, a large amount of waste heat was contained inside the UUT. Therefore, an exhaust air heat recovery (EAHR) system was proposed for the UUT. The coefficient of performance (COP) of the EAHR system for the comprehensive cabin and power cabin is 19.6%–20.3% higher than that of the traditional air source heat pump (ASHP) system. This study can provide the boundary conditions or data validation for the numerical simulation of UUTs in areas with similar climatic conditions and for subsequent research in the combined application of a UUT ventilation system and an ASHP unit.